Rapid and long-lasting reduction of crowding through training - Yashar, Amit (J Vis, 2015)
Crowding is the failure to identify an object in the peripheral visual field in the presence of nearby objects. Recent studies have shown that crowding can be alleviated after several days of training, but the processes underlying this improvement are still unclear. Here we tested whether a few hundred trials within a short period of training can alleviate crowding, whether the learning is location specific, and whether the improvement reflects facilitation by target enhancement or flankers suppression. Observers were asked to identify the orientation of a letter in the periphery surrounded by two flanker letters. Observers were tested before (pretest) and after (posttest) training (600 trials). In Experiment 1 we tested whether learning is location specific or can transfer to a different location; the training and test occurred at the same or different hemifields. In a control experiment, we ruled out alternative explanations for the learning effect in Experiment 1. In Experiment 2, we assessed different components of feature selection by training with either the same flanker polarity as the pre/posttest but opposite polarity group (flanker polarity group) or the same target polarity as the pre/posttest but opposite flanker polarity (target polarity group). Following training, overall performance increased in all four conditions, but only the same-location group (Experiment 1) and the same flanker polarity (Experiment 2) showed a significant reduction in crowding as assessed by the distance at which the flankers no longer interfere with target identification, that is, the critical spacing. These results show that training can rapidly reduce crowding and that improvement primarily reflects learning to ignore the irrelevant flankers. Remarkably, in the two conditions in which training significantly reduced crowding, the benefit of short training persisted for up to a year.